Synthesis and characterization of fluorogenic peptide substrate of HIV-1 protease based on fluorescence resonance energy transfer - Kornelyuk, A.I.; Terentiev, A.G.; Fisher, S.; Porter, T. (Биополимеры и клетка, 1995)
Synthesis of fluorogenic peptide substrate of HIV-I protease Dns-SQNYPIVWL which corresponds to the p17/p24 cleavage site for HIV-l protease have been performed. This fluorogenic substrate was based on the fluorescence resonance energy transfer between donor – Trp residue, and acceptor – dansyl group in the intact peptide. Hydrolysis of substrate by recombinant HIV-I protease resulted in the time-dependent increase of Trp fluorescence and decrease of dansyl fluorescence measured at 350 and 500 nm, respectively, due to the break of resonance energy transfer between donor and acceptor fluorophors. Hydrolysis of fluorogenic peptide substrate was studied also by reversed phase HPLC and two peptide fragments after cleavage of substrate have been detected. Kinetic constants of hydrolysis for this fluorogenic peptide substrate by HIV-I protease were calculated from Lineweaver – Burk plots: KM - 29mkM, kcat =5.4 s⁻¹ and kcat / KM -180000 M⁻¹s⁻¹. Проведено хімічний синтез флюорогенного пептидного субстрату ВІЛ-1 протеази, що має структуру Dns-SQNYPIVWL і відповідає сайту розщеплення р17/р24 у gag-поліпротеіні вірусу імунодефіциту людини.Принцип використання даного субстрату базується на резонансному переносі енергії збудження між донором – залишком Trp і акцептором – дансильною групою. Встановлено, що гідроліз флюорогенного пептидного субстрату рекомбінантною ВІЛ-1 протеазою призводить до падіння інтенсивності флюоресценції дансильної групи і одночасного зростання триптофанової флюоресценції внаслідок порушення резонансного переносу енергії між донором і акцептором. За допомогою високоефективної рідинної хроматографії в оберненій фазі зафіксовано появу пептидів, які є продуктами гідролізу субстрату. Визначено кінетичні параметри гідролізу флюорогенного пептидного субстрату ВІЛ-1 протеазою: КМ – 29 мкМ, kcat– 5,4 с⁻¹ та kcat/KM – 180 000 M⁻¹c⁻¹. Проведен химический синтез флюорогенного пептидной субстрата ВИЧ -1 протеазы , имеющей структуру Dns – SQNYPIVWL и соответсвует сайтурасщепления р17/р24 в gag – полипротеини вируса иммунодефицита людини. Принцип использования данного субстрата базируется на резонансном переносе энергии возбуждения между донором - остатком Trp и акцептором – дансильною группой. Установлено, что гидролиз флюорогенного пептидной субстрата рекомбинантной ВИЧ -1 протеазой приводит к падению интенсивности флюоресценции дансильнои группы и одновременного роста триптофановой флюоресценции вследствие нарушения резонансного переноса энергии между донором и акцептором. С помощью высокоэффективной жидкостной хроматографии в обратной фазе зафиксировано появление пептидов, которые являются продуктами гидролиза субстрата. Определены кинетические параметры гидролиза флюорогенного пептидной субстрата ВИЧ -1 протеазой : КМ – 29 мкм , kcat - 5,4 с ⁻¹ и kcat / KM – 180 000 M⁻¹c ⁻¹.